Communication Strategies for Digital Payment Adoption in Traditional Markets: Evidence from Indonesia - Diva Diamantiara Dynessa; Susan Febriantina; Nayla Putri Muzdalifah; Fahra Asri Dyta (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2026)
This study aims to evaluate the effectiveness of the communication strategy implemented by the management of Pal Meriam Market, Perumda Pasar Jaya, located in East Jakarta, in socializing the digital payment (QRIS) program to traditional merchants. A digital divide phenomenon was found, where non-food merchants reached a 90% adoption rate, while food produce merchants, representing the majority population (78% or 548 merchants), only reached 30%. This study used a qualitative descriptive approach through in-depth interviews and observations. The informants consisted of market management and traditional merchants. The results show that despite limited human resources, management optimized face-to-face interpersonal communication conducted by the Market Head during quiet hours. Furthermore, management utilized the observability principle of innovation diffusion theory by placing QRIS stickers in the stalls of successful digital adopters. This micro-visual attribute triggered social learning and reduced the passive resistance of elderly merchants who frequently cited signal disruption concerns when declining non-cash transactions. Although the persuasive approach and use of social capital effectively reduced psychological barriers, communication management still lacked an independent internal data system to guide future data-based socialization policies.